Nighttime Breastfeeding : An American Cultural Dilemma - CecÃlia Tomori (Berghahn Books, 2014)
The book is divided into seven chapters, followed by a brief conclusion. Each chapter offers a specifi c set of arguments that draw on a diverse set of literatures in order to illuminate different aspects of my research. These chapters can be seen as bits of mirrored glass that, while they each provide a unique vantage point, when placed together constitute a larger mosaic of one particular perspective on the cultural dilemmas of nighttime breastfeeding and sleep in the United States. The seven body chapters are loosely organized into four parts. The fi rst part comprises a single chapter that lays the groundwork for my anthropological approach to nighttime breastfeeding. Drawing on a diverse body of sociocultural and medical anthropological scholarship I develop the concept of â€œembodied moral dilemmasâ€ raised by nighttime breastfeeding as a lens through which we can glean unique insight into the complex dynamics of American personhood, family relations, biomedicine, and the far-reaching effects of capitalism. While I have attempted to make my discussion of the relevant concepts accessible, readers unfamiliar with the discipline of anthropology may fi nd this chapter challenging. These readers may wish to move forward to the next chapters, in which I pursue the above themes through historical and ethnographic examples. I welcome readers to dip back into this chapter based on their interest.